1988
DOI: 10.1254/jjp.46.183
|View full text |Cite
|
Sign up to set email alerts
|

A new method for studying working memory by using the three-panel runway apparatus in rats.

Abstract: Abstract-We designed a new method for studying working memory, by using a repeated acquisition procedure in the three-panel runway apparatus. This ap paratus is composed of a start box, a goal box and four consecutive choice points; each choice point consists of three panel gates.Male Wistar rats were trained with 6 consecutive trials (one session) per day. Each trial was performed every two minutes.In this apparatus, rats could pass through only one gate (correct gate) among three panel gates in the direction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 20 publications
(2 reference statements)
1
20
0
Order By: Relevance
“…However, as Hodges [89] argues, the role of motivation in spatial learning is not clear, as working memory tasks in different food reward mazes (i.e. RAM and 3-door runway) result in different performances in hippocampal lesioned animals [61,92,98]. Nevertheless, stress is likely to be a key confounding factor in cognitive performance in spatial memory tasks.…”
Section: Comparison Between the Radial Arm Maze And Morris Water Mazementioning
confidence: 99%
“…However, as Hodges [89] argues, the role of motivation in spatial learning is not clear, as working memory tasks in different food reward mazes (i.e. RAM and 3-door runway) result in different performances in hippocampal lesioned animals [61,92,98]. Nevertheless, stress is likely to be a key confounding factor in cognitive performance in spatial memory tasks.…”
Section: Comparison Between the Radial Arm Maze And Morris Water Mazementioning
confidence: 99%
“…Systemic scopolamine also deteriorates working memory in the three-panel runway task (10,11). Okaichi et al (31) reported that scopolamine impairs not only the working memory but also the reference memory of rats in the eight-arm radial maze with 4 arms baited.…”
Section: Discussionmentioning
confidence: 99%
“…Working and reference memory were assess ed by a three-panel runway apparatus (10,11). The apparatus (175 X 36 X 25 cm, length X width X height) is composed of a start box, a goal box, and four consecutive intervening choice points.…”
Section: Three-panel Runway Taskmentioning
confidence: 99%
See 2 more Smart Citations